Actualization of Policy Deconstruction: Handling Overseas Refugees in Kupang City - Emanuel Kosat; Veronika Ina Assan Boro; Frans Bapa Tokan; Urbanus Ola Hurek (Dinasti Research, 2024)
This research is intended to discover the various injustices that befell foreign refugees in Kupang City. Injustice with a regulative paradigm is carried out by actors making public policy. In reality, refugees from women and children are objects who twice experience injustice from policies that at first glance appear to be impartial and impressive, but on the other hand are another form of oppression. This research departs from a post-positivistic paradigm, using inductive logic. The findings from this research are an effort to deconstruct the logic and ethics of policies that make refugees vulnerable, whether in their countries of origin or transit/destination countries. The results of the research prove that the factor behind the policy corpus actually resides in gender hegemonic behavior in the humanitarian balance, as well as the plight of refugee women and children becoming increasingly vulnerable when placed vis a vis climate adaptation.